Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011054
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral contraceptives: the risk of myocardial infarction and ischemic stroke

Abstract: Combined oral contraceptives: the risk of myocardial infarction and ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 25 publications
1
35
0
9
Order By: Relevance
“…The authors of the recent Cochrane review suggested that pills containing 30 mg of EE or less are the safest form of hormonal contraception, and available evidence suggests that 20 mg EE CHCs confer even lower risk. 41 Although all of the studies in this review found an increased risk of stroke in women with migraine who used CHCs, it should be noted that the absolute risk of stroke in reproductive-aged women is low. The crude, unadjusted incidence of stroke was 3.56 per 100,000 women of reproductive age per year in the UK population-based study by Nightingale and Farmer, and this is consistent with other studies specifically evaluating incidence in premenopausal women.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The authors of the recent Cochrane review suggested that pills containing 30 mg of EE or less are the safest form of hormonal contraception, and available evidence suggests that 20 mg EE CHCs confer even lower risk. 41 Although all of the studies in this review found an increased risk of stroke in women with migraine who used CHCs, it should be noted that the absolute risk of stroke in reproductive-aged women is low. The crude, unadjusted incidence of stroke was 3.56 per 100,000 women of reproductive age per year in the UK population-based study by Nightingale and Farmer, and this is consistent with other studies specifically evaluating incidence in premenopausal women.…”
Section: Discussionmentioning
confidence: 78%
“…A more recent Cochrane review looked at 24 studies evaluating the effect of oral contraceptives on risk of myocardial infarction and ischemic stroke. 41 They also concluded that there is a risk of ischemic stroke with use of oral contraceptives, but a dose response was seen. The OR for risk of ischemic stroke or MI with 20 mg EE was 1.6 (95% CI 1.4-1.8), for 30-49 mg EE 2.0 (1.4, 3.0), and for >49 mg 2.4 (1.8, 3.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there has been debate 8,9 about whether different progestins impact the risk of venous thromboembolism differently the chosen progestin does not appear to affect arterial risks such as CVA or MI. 10 For an in-depth review of this issue, we will examine 3 sources: (1) a recent systematic review 6 of hormonal contraceptives in women with migraine (this was selected as an example of the typical systematic review of this topic; concerns and flaws will be pointed out as we go along), (2) a recent study 11 that specifically compares the safety of three discrete, new CHC formulations with an accepted low-risk option (this article was selected because it exemplifies the way CHCs should be compared as we go forward-specifically and individually rather than lumped together as "CHCs"), and (3) the most recent Cochrane review of stroke risk and CHCs. 10 Let's first examine the most recent 6 of the typical systematic reviews, taking a closer look at each selected article to identify confounding issues.…”
Section: Stroke Risk Related To Chcs: the Estrogen Dose Mattersmentioning
confidence: 99%
“…And, finally, we have the 2015 Cochrane Review, 10 which identified 1,298 publications assessing arterial risks in CHC users compared with nonusers. In their network meta-analysis, they included 28 publications reporting on 24 studies.…”
Section: Cochrane Reviewmentioning
confidence: 99%